Theory of Behaviorism In Learning Arabic Language - Abdul Hafidz bin Zaid; Dyah Purnama Ketty (Universitas Pahlawan Tuanku Tambusai, 2022)
Behaviorism learning theory is oriented towards measurable and observable result, Behaviorism emphasizes behavior change based on the principle of stimulus and response. This study aims to describe the teory of behaviorism and its application in learning Arabic, this research is a conceptual study using descriptive-qualitatif methode. The research result is: 1) Behaviorism theory is the theory of behavior development measured and observed that results from responding to student’s incentives, 2) Developing the ability to start speaking to learners without waiting for the development of their linguistic wealth and the ability to accomplish, developing the ability of learners to innovate and act on different situations training the student to communicate actively with Arabic speakers and encourage the student to speak a language other than his own in front of his colleagues.